Literacy, Personal Development, and Social Development Among Latina Youth: Exploring the Use of Latino Literature and Dance. Issue 2 (2nd July 2016) - Cook, Amy L.; Hayden, Laura A.; Denitzio, Kari
Abstract : A culturally responsive group counseling intervention was conducted that merged literacy acquisition with personal and social development. Employing an embedded mixed methods design, 20 fifth-grade Latina students were randomly assigned to engage in an 18-week group counseling curriculum consisting of culturally meaningful readings, discussions, and physical activities involving Latino literature and dance (n = 10) or to attend character enrichment, serving as the active control (n = 10). A two-group quasi-experimental analysis using non-parametric tests indicated a significant improvement in literacy grades but limited change in personal and social development among intervention participants. No significant differences in literacy grades were found between intervention and active control groups. Feasibility and service outcomes were examined through completion of group leader checklists, student and educator surveys, and semi-structured interviews with parents. Findings warrant further examination of employing cultural sensitivity with Latina youth in counseling group work.